Investigation of the Binding Affinity of a Broad Array of l-Fucosides with Six Fucose-Specific Lectins of Bacterial and Fungal Origin - Thai Le, Son; Malinovska, Lenka; Vašková, Michaela; Mező, Erika; Kelemen, Viktor; Borbás, Anikó; Hodek, Petr; Wimmerová, Michaela; Csávás, Magdolna (Molecules (Basel, Switzerland), 2019)
Series of multivalent α-l-fucoside containing glycoclusters and variously decorated l-fucosides were synthesized to find potential inhibitors of fucose-specific lectins and study the structure-binding affinity relationships. Tri- and tetravalent fucoclusters were built using copper-mediated azide-alkyne click chemistry. Series of fucoside monomers and dimers were synthesized using various methods, namely glycosylation, an azide-alkyne click reaction, photoinduced thiol-en addition, and sulfation. The interactions between compounds with six fucolectins of bacterial or fungal origin were tested using a hemagglutination inhibition assay. As a result, a tetravalent, α-l-fucose presenting glycocluster showed to be a ligand that was orders of magnitude better than a simple monosaccharide for tested lectins in most cases, which can nominate it as a universal ligand for studied lectins. This compound was also able to inhibit the adhesion of Pseudomonas aeruginosa cells to human epithelial bronchial cells. A trivalent fucocluster with a protected amine functional group also seems to be a promising candidate for designing glycoconjugates and chimeras.
Keywords: Humans; hemagglutination; hemaglutinace; Structure-Activity Relationship; fungální proteiny; vztahy mezi strukturou a aktivitou; Protein Binding; Hemagglutination Inhibition Tests; lektiny; lidé; fukosa; Hemagglutination; Fucose; bakteriální proteiny; l-fucosides; multivalency; lectins; Lectins; glycoclusters; cystic fibrosis; vazba proteinů; testy inhibice hemaglutinace; Bacterial Proteins; Fungal Proteins